Timothy Curry: capstone - Curry, Timothy, artist (Colorado State University. Libraries, 2017)
The artist's statement: When I am creating a design I find the fact that there is a connection between the client and the design. I use the design programs Illustrator and Indesign. I come up with most of the ideas for my design when I am in the comfort of my own home. This is where my creative juices start to flow. I begin with sketches and after the sketches, I plug in the ideas into the programs. What inspires my work is myself. I like to try and push my creativity past the threshold and have that ability to create any design for any client. My work is an examination of different ideas. I designed many different designs, having them look great for the viewers and the client.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.